Development and Integration of a Post Impact Control Function for Passenger Vehicles - GAO, YONGWEI; YAO, MENG (My University, 2014)
The thesis further develops a Post Impact Stability Control (PISC) function so as to improve the performance to avoid multiple-event accidents. The function is integrated in a vehicle dynamics control architecture. The high-level control target is set to minimize the maximum lateral deviation from the initial desired path. This is achieved by integrating an active steering control strategy with the existing electronic stability control function (ESC). The control task is realized by active control of front steering angle and individual wheel braking. The integrated PISC function is verified across various post-impact kinematics conditions, using a high-fidelity vehicle simulation model in CarMaker®. A vehicle states estimator is designed using a simplified 3-DOF two-track vehicle model. This estimator is essential for testing real-time implementation concepts. It was found that a well-estimated vehicle lateral velocity is important to guarantee a well-performed PISC function. The controller is also compared favourably to the other benchmark functions, i.e. PIB and PISC(without integration of ESC). Towards real-time implementation, two active steering configurations are simulated: Steer-by-Wire and Electronic Power Assist Steer (EPAS). It was found that the control performance is generally not sensitive to the steering actuators. However, increased limit of steering torque overlay is shown to improve the minimization of lateral derivation, without introducing control instability.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering